Polarization observables in rare decay B->K*(->K Pi )l+l- (International Journal of Mathematics and Physics, 2016)
Our article is devoted to the study of the B->K*(->K Pi )l+l- decay. Rare decay B->K*(->K Pi )l+l- is one of the best modes to search for new physics beyond the Standard Model (SM). A large number of observables allow for unique tests of the SM contributions. We calculate the relevant form factors in the framework of the covariant quark model with infrared confinement in the full kinematical momentum transfer region. The calculated form factors are used to evaluate branching fractions and polarization observables in the cascade decay B->K*(->K Pi )l+l-. We compare the obtained results with available experimental data and the results from other theoretical approaches. We show the relation of our helicity formalism with an approach based on the transversality amplitudes which is widely used by both experimentalists and theorists.
Keywords: relativistic quark model; confinement; B-meson; rare decay; form factor; polarization observables.